Current issues in phraseology - Hoffmann, Sebastian; Fischer-Starcke, Bettina; Sand, Andrea (Linguist) (Benjamins current topics ;, 2015)
This paper explores ways in which research into collocation should be improved. After a discussion of the parameters underlying the notion of collocation, the paper has three main parts. First, I argue that corpus linguistics would benefit from taking more seriously the understudied fact that collocations are not necessarily symmetric, as most association measures imply. Also, I introduce an association measure from the associative learning literature that can identify asymmetric collocations and show that it can also distinguish collocations with high and low association strengths well. Secon.